Manpower Training Needs Analysis of the Bamboo Furniture Industry in Luzon Island, Philippines - Roxas, Jilian O. (1990)
A survey was conducted on the manpower· training needs of the bamboo furniture industry in the selected provinces of Luz on Island, Philippines. The general objective was to generate data on industrial manpower as a basis for designing and conducting appropriate training courses aimed at improving manpower competencies in bamboo furniture industries. All the bamboo furniture producers and exporters belong to cottage-type industries with capitalization of P500 to P200,000. Majority of them (55.4%) have invested up to P10,000 in furniture industry compared with those whose capital ranges P10,000 to P50,000 (34.4%) and over P50,000 (10.2%). Family ownership is the most common among the respondents, followed by single proprietorship and the least by a corporation. The respondents are involved in mass production and made-to-order items, the most saleable of which being the sala set. "Management Planning and Control" is perceived as the most relevant competency category in relation to job performance and all the rest are not relevant. For future training, "Management Planning and Control" and "Technological Innovations" are rated most relevant while the other three categories are not relevant. Despite the prof its derived from bamboo furniture industry, the furniture makers are confronted with many problems. The producers are characterized by lack of entrepreneurial management skills, inadequate knowledge of bamboo drying, lack of storage facilities and poorly-maintained equipment/tools, inadequate knowledge of product design development and finishes / finishing techniques, and lack of quality control. The exporters are faced with lack of institutional support, financial management problems and inadequate knowledge of markets/marketing strategies. In order to minimize these problems, intensive information campaign on available technological innovations should be conducted by the technology - generating institutions. Likewise, financing / lending institutions should devise simple borrowing schemes more adapted to the limited business capability of the small furniture manufacturers.